2012
DOI: 10.1182/blood-2011-10-388629
|View full text |Cite
|
Sign up to set email alerts
|

Cell lineage analysis of acute leukemia relapse uncovers the role of replication-rate heterogeneity and microsatellite instability

Abstract: Human cancers display substantial intratumoral genetic heterogeneity, which facilitates tumor survival under changing microenvironmental conditions. Tumor substructure and its effect on disease progression and relapse are incompletely understood. In the present study, a highthroughput method that uses neutral somatic mutations accumulated in individual cells to reconstruct cell lineage trees was applied to hundreds of cells of human acute leukemia harvested from multiple patients at diagnosis and at relapse. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 46 publications
3
60
1
Order By: Relevance
“…The previous platform (Reizel et al , 2012Shlush et al 2012) was based on small multiplex groups (4×) using fluorophores and different MS lengths in CE, similarly to the protocol used for forensic analysis. The platform presented here demonstrates an immense advancement over our previous lineage analysis platform:…”
Section: Wwwgenomeorgmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous platform (Reizel et al , 2012Shlush et al 2012) was based on small multiplex groups (4×) using fluorophores and different MS lengths in CE, similarly to the protocol used for forensic analysis. The platform presented here demonstrates an immense advancement over our previous lineage analysis platform:…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…Most of the MS panel is designed for (A) MSs of type AC on the X Chromosome to allow for monoallelic MS calling Wasserstrom et al 2008;Reizel et al 2011;Segev et al 2011;Shlush et al 2012) and for (B) the longest MS loci possible, which exhibit a higher mutation rate in vivo (Ellegren 2004;Supplemental Table S2). Notably, primers were designed such that the entire MS will be covered within a 150-bp Examples of single-cell analyses to reconstruct clonal/lineage analysis Wang et al 2012;Xu et al 2012;Gawad et al 2014;Lohr et al 2014;Lodato et al 2015) (Navin et al 2011;Cai et al 2014;Wang et al 2014) ) Salipante et al 2010;Reizel et al 2011Reizel et al , 2012Shlush et al 2012;Evrony et al 2015) read (see Methods). (2) We modified the second PCR to apply a sample barcode by utilizing combinations of forward and reverse PCR primer combinations, resulting in a dual indexed NGS library (Supplemental Fig.…”
Section: A Generic Cell Lineage Analysis Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistant clones were only a minor fraction at the time of diagnosis and were the result of branching evolution. Accordingly, studies in T-cell acute lymphoblastic leukemia, 3 acute myeloid leukemia, 4 and chronic lymphocytic leukemia 5 all suggested that resistant clones originated from ancestral minor populations. This is of no surprise at all, as most of the current treatment protocols aim at eliminating the major population observed at diagnosis.…”
mentioning
confidence: 99%
“…In humans, analysing the genetic variation in individual tumor cells has provided insights into the evolutionary development of cancer cells, thus identifying mechanisms causing relapse (Shlush et al, 2012). …”
Section: Single Cell Genomicsmentioning
confidence: 99%